Preparasi dan Karakterisasi Katalis CoMo/H-Zeolit Y - Musta, Rustam (Jurnal Fisika FLUX, 2010)
Preparation and characterization of catalyst CoMo/H-zeolite Y hasbeen done. Catalyst was prepared from NH4Y-zeolite then heated 115oC for 1 hto eliminate water then calcined at 550oC for 2 h to evaporate ammonia,produced HY-zeolite (HYZ) sample. Impregnation of CoMo metals on the HYZsample was done by co-impregnation method, where the HYZ (10 g) was mixedwith (NH4)6MO7O24.4H2O in 24 mL aquabidest and 3 mL of ammonia thenstirred of 60oC for 2 h. This mixture was then mixed with Co(NO3)2.6H2O in 24mL aquabidest and 3 mL of ammonia then stirred of 60oC for 2 h. The resultingsample was filtered and dried. The dried sample was then calcined under N2stream at temperature of 550oC for 2 h, followed by oxidized with O2 thenreduced with H2 stream at temperature 400oC for 2 h, respectively producedCoMo/HY catalyst. Characterization of the catalyst included analysis of NH3groups was done with by infra red spectrofotometry (IR), the crystallinity with Xraydiffraction (XRD) and the acidity was calculated with NH3 absorption bygravimetry method, metal content on the catalyst was determined by atomicabsorption spectroscopy (AAS). FTIR result of CoMo/HY catalyst showed thatdisappeared ammonia was after heating. The XRD date indicated the increase ofcatalyst crystallinity as the following: NH4Y< died NH4Y < HY< CoMo/HY.CoMo/HY catalyst has average acidity = 6,87 mmol/g where as the HY hasaverage acidity = 7,66 mmol/g. The metal content in the HY was 8023 and 7681ppm, for Co and Mo respectively.